DEVELOPMENT OF LIFE INSURANCE MARKET IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Tretiak K.V., Demchenko V.O. DEVELOPMENT OF LIFE INSURANCE MARKET IN UKRAINEPurpose. The aim of the article is to study the main problems faced by the domestic life insurance market, substantiation of the negative impact and identification of opportunities for its future development.Methodology of research. The research is based on scientific and practical developments of scientists and specialists. The following methods are used to achieve this purpose, among them are analytical (when analyzing the main components of the life insurance market); generalization (when compiling data on the assessment of the life insurance services segment functioning in order to identify patterns of its trends); evaluation and inference (to summarize the subject of the research).Findings. Insurers’ dynamics in the domestic insurance market in recent years in terms of their numbers have been analyzed; an assessment of the structure in terms of gross and net insurance premiums and payments has been substantiated. The comparative characteristics of digital indicators of the Ukrainian and European life insurance markets have been considered. The issue of inclusion of insurance services in social programs and urgent deterrents of its solution in Ukraine has been studied. The advantages and disadvantages of life insurance areas (the accumulative pension, the insurance against accidents at work) have been analyzed. An assessment of the composition of the social package in the Ukrainian insurance market and the importance of each component, namely the basic social guarantees and additional material benefits, taking into account the available potential has been done.Originality. Theoretical and practical foundations of life insurance market development have been deepened on the basis of cooperation between the state, which at the same time assumes responsibility for maintaining the minimum income of all citizens, and also maximally stimulates the development of various forms of non-state insurance in order to save life, health and income.Practical value. The results of the research can be the basis for future scientific exploration in the field of effective development and functioning of the life insurance market.Key words: insurance, life insurance, accumulative pension insurance, insurance of working accidents, life insurance market.
Keywords: Key words; insurance; life insurance; accumulative pension insurance; insurance of working accidents; life insurance market.